Acknowledging the elephant in the room: how stressful environmental contexts shape relationship dynamics. (February 2017) - Neff, Lisa A; Karney, Benjamin R
Highlights: Risk for marital distress is significantly greater for lower income couples. Lower income marriages develop in a context filled with negative stressors. Stressful events outside the marriage create more problems within the marriage. Stressful events also hinder spouses' capacity to address problems constructively. Interventions targeting the stress of economic hardship may aid marital outcomes. Abstract : Compared to affluent marriages, lower income marriages develop within a context filled with negative stressors that may prove quite toxic for marital stability. The current paper argues that stressful contexts may undermine marital well-being through two routes. First, external stressors create additional problems within the marriage by diverting time and attention away from activities that promote intimacy between partners. Second, external stress may render spouses ill-equipped to cope with this increase in problems by draining spouses of the energy and resources necessary for responding to marital challenges in a constructive manner. In acknowledging the role of the marital context for relationship dynamics, this model suggests new directions for interventions designed to strengthen the marriages of lower income couples.